Canaanite Dagon: Origin, Nature - Montalbano, Frank J.
1. Old Accadian Period (с. 2360-2180 B. С.) — 2. Neo-Sumerian Period (с. 2070-1960 B. С.) — 3. Dynasty of isin and Larsa (с. 1960-1830 B. С.) — 4. The Epoch of Hammurabi (1728-1530 B. С.) — 5. Canaanite Sources — 6. Later Assyro-Babylonian Inscriptions (900-640 B. С.).